Estimates for Dirichlet Eigenvalues of Divergence Form Elliptic Operators in Non-Lipschitz Domains; Journal of Mathematical Sciences; Vol. 268, iss. 3 - Goldshteyn V. M. Vladimir Mikhaylovich (2022, 2022)
Title screen